PROSES PENGEMBANGAN DAN IMPLEMENTASI INOVASI DAERAH - Setiawan, Arif; Muhammad Rendy; Andika Dwi Nurliansyah; Zidni Muhammad Ardiansyah; Putra Janaz Alfinalis; Adi Purnomo (BRIN (Badan Riset dan Inovasi Nasional), 2024)
Regional innovation plays an important role in improving the quality of public services, considering the challenges and needs of an increasingly dynamic society. This article discusses the process of developing and implementing regional innovation with the aim of increasing the effectiveness and efficiency of public services. The main stages in developing this innovation include identifying community needs and problems, research and solution development, strategic planning, implementation, as well as evaluation and continuous improvement. Each challenges related to technology infrastructure that is evenly distributed throughout the region and the level of digital literacy of the community that needs to be improved. Overall, the implementation of E-Government in stage requires active involvement from various stakeholders, such as society, academics, government and the private sector, to create relevant and sustainable solutions (Zunaidi, 2024). The results of the discussion show that the success of regional innovation depends on careful planning, policy support, human resource competence, and community involvement in the process (Ramadhani et al., 2024). By following a systematic development process, regional innovation can have a significant impact on improving the quality and accessibility of public services, as well as increasing community satisfaction..